Hubungan Pola Asuh Dengan Self Confidency Anak Usia Prasekolah Di Tk Dharma WanitaDesa Segunung Kecamatan Dlanggu Kabupaten Mojokerto - Murtiyani, S.KM., S.Kep., Ns., M.Kes, Ninik; Suidah, S.Kep., Ns., M.Kes, Hartin (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AsbtractThe childs independence is an individuals ability to continue to learn in dealing with various environmental situations, so that they can think and act on their own. Children who arc not independent will negatively affect the development of his personality. facts in TK Dharma Wanita Dcsa Scgunung, they found preschoolers who can not do toilet training and still escorted by parents today want DAB I BAK, parents must be in class when school children, and cry at school if the parent is not visible when they are looking for. The purpose of this study was to analyze the influence of parenting to the confidence of preschool children in TK Dharma Wanita A mountain village of Subdistrict Dlanggu Mojokerto. The design study is a cross-sectional analytic. The population is all the parents and all the preschoolers in TK Dharrna Wanita many as 17 people. The dependent variable in this study are confident preschoolers. The independent variables in this study is the parents parenting preschoolers. The collection of data about parenting questionnaire used closed while for confidence to preschoolers using observation sheet. The data were processed using pearson test with the level of allowable error u = 0.05. From the test results obtained pcarson statistic significance value of 0.005. Because the significance value obtained <a. (0.05) then the research hypothesis HI accepted which means that there is the influence of parenting to the confidence of preschool children in kindergarten Dhanna Wanita A mountain village of Subdistrict Dlanggu Mojokerto. The existence of good parenting, supported by a conducive environment that will motivate children lo grow more confident. Besides, a strong impetus from the parents and the child is much faster in the learning process will facilitate the emergence of a strong sense of confidence. When the children get good parenting and appropriate from the parents, then the child will form his confidence is high.Keywords: Parenting, Confidence, Preschooler